2014
DOI: 10.1016/j.micinf.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced DNA damage and damage-induced inflammation: a vicious cycle

Abstract: Inflammation is the ultimate response to the constant challenges of the immune system by microbes, irritants or injury. The inflammatory cascade initiates with the recognition of microorganism-derived pathogen associated molecular patterns (PAMPs) and host cell-derived damage associated molecular patterns (DAMPs) by the pattern recognition receptors (PRRs). DNA as a molecular PAMP or DAMP is sensed directly or via specific binding proteins to instigate proinflammatory response. Some of these DNA binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 166 publications
0
43
0
Order By: Relevance
“…Persistent DNA damage, including oxidative damage, is well known to stimulate the production of inflammatory mediators (Chatzinikolaou et al, 2014;Palmai-Pallag and Bachrati, 2014), a dynamic that is exacerbated by DNA repair deficiency (Karakasilioti et al, 2013). Furthermore, Yanagi and co-workers have reported that ubiquitinated FANCD2 inhibits NF-κB transcriptional activity and suppresses transcription of the TNF-α gene (Matsushita et al, 2011).…”
Section: Why Is Ros Production Elevated In Fa?mentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent DNA damage, including oxidative damage, is well known to stimulate the production of inflammatory mediators (Chatzinikolaou et al, 2014;Palmai-Pallag and Bachrati, 2014), a dynamic that is exacerbated by DNA repair deficiency (Karakasilioti et al, 2013). Furthermore, Yanagi and co-workers have reported that ubiquitinated FANCD2 inhibits NF-κB transcriptional activity and suppresses transcription of the TNF-α gene (Matsushita et al, 2011).…”
Section: Why Is Ros Production Elevated In Fa?mentioning
confidence: 99%
“…Consequently, FA patients at an early age phenocopy the inflammaging of normal aging, suggesting that FA should be characterized as a premature inflammaging disorder, from which flow the pathologies that overlap with those of normal aging (see above) ( Figure 1 ). Since DNA damage can induce inflammation and inflammation can provoke DNA damage (Palmai-Pallag and Bachrati, 2014), FA patients are trapped in a downward spiral.…”
Section: Why Is Ros Production Elevated In Fa?mentioning
confidence: 99%
“…For instance, extracellular histones, in addition to being bactericidal, can also kill eukaryotic cells and induce tissue toxicity and thrombosis [16e18]. Circulating cell free double strand DNA is recognized as a "danger-associated molecular pattern" (DAMP) and can induce an exaggerated activation of innate immunity, whereby inflammation-induced DNA damage and DNA-induced inflammation form a vicious cycle [19]. As a result, NETosis and NET-associated components can induce tissue damage.…”
Section: The Dark Side Of Netosismentioning
confidence: 99%
“…This can promote genomic instability characterized by defects in DNA repair and accumulation of DNA damage 30,31. To test whether vitamin D deficiency initiates DNA damage in myometrial tissues, we performed immunohistochemical analyses using immunoreactive γH2AX (a DNA damage marker) via polyclonal anti-γH2AX antibodies (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%